A review of wastewater treatment using natural material and its potential as aid and composite coagulant - Siti Nor Aishah Mohd-Salleh; Nur Shaylinda Mohd-Zin; Norzila Othman (Penerbit Universiti Kebangsaan Malaysia, 2019)
The introduction of natural materials into the coagulation-flocculation process need to be practiced as common as possible. The previous literature indicated that utilization of natural material is actually worth to be developed and if possible, into the commercial one. However, the application of natural coagulants itself as the primary treatment is not sufficient, due to the rise in constraints which limited its performance. Emerging technologies and depth studies are actually helping these limited conditions to grow them as good as the performance of chemical coagulants. Alternatively, the natural-based coagulants are commonly used as coagulant aids alongside chemical coagulants, which have created a highlight in water research. This review covers the type of coagulants used in the coagulation-flocculation of wastewater treatment especially in the usage of natural-based coagulants. This review paper also outlines the future prospects of natural materials as aids and its potential as sustainable composite coagulants.